Morphogenetical, structural and functional plastic responses to simultaneous shading and phosphorous shortage during establishment of Trifolium repens L. - Gatti, María Laura; Cornaglia, Patricia Susana; Re, Paula (Springer, 2025)
The enrichment with Trifolium repens L. (white clover), could fulfill an ecological and productive function in humid-temperate silvopastoral systems in South America. The objective was to describe the morphogenetic, structural and functional changes of two white clover large-leafed cultivars under simultaneous shading and phosphorus shortage during establishment. A pot trial designed in 3 randomized complete blocks was carried out in sub-subdivided plots. The main plot was the shading treatment (4 levels: full sun = 0% and 30%, 60% and 90% of shading (shade), sub-plots were 2 cultivars (Junín and El Lucero) and sub-sub-plots, were 2 phosphorous conditions (without P− and with added P+). At final harvest the number of primary and secondary stolons and the length of their internodes, the number of leaves and length of petioles were counted. The light threshold was on 60% of shading; mean total daily PAR > 15.3 mol m−2 day−1. This light threshold was the same under P+ or P−. The number of stolons and length of internodes remained between full sun and 60% shade but the length of petioles increased. The lower number of expanding leaves was compensated by a lower number of senescent ones that mantained the living leaves and leaf area of the plants up to 60% of shading. P shortage did not limit the number of primary or secondary stolons, the number of leaves or petiole length, so the horizontal or vertical occupation was slightly affected. Both cultivars responded similarly. White clover would be a promising species for these systems.